Temperature evaluation of a hyper-rapid plasma jet by the method of high-speed video recording - Rif A. E.; Cherevko V. V.; Ivashutenko A. S. Alexander Sergeevich; Martyushev N. V. Nikita Vladimirovich; Nikonova N. Ye. (Integrated Computer Control Systems in Mechanical Engineering, 2016)
Title screen